Four New Brazilian species of Begonia (Begoniaceae) - Jacques, Eliane De Lima (Phytotaxa, 2018)
Four new species of the genus Begonia (Begoniaceae) from Brazil are described and illustrated. Begonia itingae, B. mamedeana, and B. tripicoensis are endemic to the Atlantic Forest, an area with high species richness and endemism; B. rivularis is endemic to the central region of this country.